A Review on Halide Perovskite Film Formation by Sequential Solution Processing for Solar Cell Applications. Issue 4 (2nd April 2020) - Bing, Jueming; Huang, Shujuan; Ho-Baillie, Anita W. Y.
Abstract : A general overview of sequence deposition for perovskite film formation is provided, followed by a focused review on sequence solution processes. Between 2013 and 2019, there have been more than seventy studies on perovskite sequential solution processes alone. Key strategies for improving perovskite film quality for improving performance of associated solar devices are discussed. More details can be found in article number 1901114 by Anita W. Y. Ho‐Baillie and co‐workers.